HUBUNGAN PERHATIAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Rianita Simamora (Universitas Islam Sumatera Utara, 2021)
This study aims to determine the influence of parental attention and learning motivation on mathematics learning outcomes of seventh-grade students of SMP Negeri 1 Pematangsiantar. Parental attention and learning motivation data obtained from an instrument in the form of a closed questionnaire distributed online via google form with good quality because it is valid and reliable. Meanwhile, students' mathematics learning outcomes were obtained from the school's documentation of grades. The test results show that there is a direct effect of parental attention on learning motivation with a t-count of 2.1309 and a significance level of 0.08325; there is a direct effect of parental attention on student mathematics learning outcomes with a t-count of 2.42875 and a significance level of 0.13768; there is an indirect effect of learning motivation on student mathematics learning outcomes with a t-count of 2.58298 and a significance level of 0.14988; there is an indirect effect of parental attention and learning motivation on mathematics learning outcomes. As for the contribution given by parents' attention and learning motivation to mathematics learning outcomes was 28.75% and the total effect was 42.327%. Therefore, the higher parental attention and student motivation, the higher the learning outcomes.